In-cloud processing as a possible source of isotopically light iron from anthropogenic aerosols: New insights from a laboratory study. (15th August 2021) - Mulholland, Daniel Santos; Flament, Pascal; de Jong, Jeroen; Mattielli, Nadine; Deboudt, Karine; Dhont, Guillaume; Bychkov, Eugène
Abstract: Wet atmospheric deposition can account for up to 50% of the total iron input to surface waters, so establishing the extent to which kinetic and equilibrium isotope effects can influence aerosol soluble δ 56 Fe values is imperative to trace and constrain aerosol sources using Fe isotopes and to understand the differences found between δ 56 Fe values for bulk and soluble phases of aerosols. In this context, changes in iron solubility and isotopic composition of dissolved Fe during simulated atmospheric processing of industrial ash was investigated. Kinetic and equilibrium experiments were performed under UV/VIS light using ash from a Fe–Mn alloy metallurgical plant and a synthetic solution that mimics cloud water chemistry. The nature of the Fe species of the industrial ash was investigated by Mössbauer Spectroscopy, whereas ash and dissolved δ 56 Fe values were measured by MC-ICP-MS. Mössbauer Spectroscopy revealed that α-hematite, magnetite, and poorly crystallized manganoferrite nanoparticles are the main Fe species. In the early-stage dissolution (until 60 min) a Fe isotope fractionation (Δ 56 Fesolution-bulk ash ) of −0.284 ± 0.103‰ was found at the minimum contact time evaluated herein (i.e., 5 min) due to kinetic isotopic effects. In the late-stage dissolution (after 60 min) a Δ 56 Fesolution-ash of 0.227 ± 0.091‰ was found due to equilibrium isotopic effects. The kinetic isotope effect within one ash surface monolayer was modeled with an enrichment factor ( ε ) of −1‰ in 56 Fe/ 54 Fe ratio. Iron fractional dissolution undergone during different atmospheric processing time scales may release Fe with contrasted isotope compositions to solution, changing the original soluble Fe isotope signature (which is linked to its source). This might be especially important when the dissolution process goes from kinetic to near-equilibrium conditions, in which higher amounts of Fe are progressively released from ash surface. Graphical abstract: Image 1 Highlights: Early-stage dissolution releases isotopically light Fe in solution. Ligand and reductive ligand-promoted dissolution controls Fe isotope fractionation. Equilibrium dissolution forms an isotopically heavy soluble Fe pool. δ 56 Fe values of aerosol soluble Fe phases can be different from source to sink.